Price discovery in Canadian and US 10-year government bond markets - Bryan Campbell; Scott Hendry (Bank of Canada, 2007)
This paper presents some new results on the price discovery process in both the Canadian and U.S. 10-year Government bond markets using high-frequency data not previously analyzed. Using techniques introduced by Hasbrouck (1995) and Gonzalo-Granger (1995), we look at the relative information content of cash and futures prices in the market for Canadian Government bonds using futures market data from the Montreal Exchange and OTC cash market data reflecting the inter-dealer market covered by CanPx. We also analyze similar data from the US market over a somewhat longer period using data on the Chicago Board of Trade (CBOT) futures market as well as the cash market from GovPx in the first part of the sample and subsequently from BrokerTec. In general, we find that relatively more price discovery occurs in the futures markets than the cash markets in both Canada and the U.S. and that the results look remarkably similar across the two countries despite the large differences in the sizes of their markets and in their characteristics, particularly on the cash side. These overall results, however, hide the fact that information shares for the U.S. futures markets declined throughout 2004-05 apparently as a result of improvements in the spot market BrokerTec platform. Day-to-day variation in price discovery information shares is related to bid-ask spreads, trading volumes, and realized volatility in the markets but there remains much unexplained.
Keywords: G12; G13; G14; 330; Financial markets; Market structure and pricing; Finanzmarkt; Rentenmarkt; Preis; Geldmarkt; Termingeschäft; USA; Kanada